3D Simulations of Ultra-small MOSFETs with Real-space Treatment of the Electron – Electron and Electron-ion Interactions. Issue 4 (2000) - Gross, W. J.; Vasileska, D.; Ferry, D. K.
Abstract : We present a 3D Ensemble Monte Carlo particle-based simulator with a novel realspace treatment of the short-range electron – electron and electron-ion interactions. By using a corrected Coulomb force in conjunction with a proper cutoff range, the shortrange portion of the force is properly accounted for, and the 'double counting' of the long-range interaction is eliminated. The proposed method naturally incorporates the multi-ion contributions, local distortions in the scattering potential due to the movement of the free charges, and carrier-density fluctuations. The doping dependence of the low-field mobility obtained from 3D resistor simulations closely follows experimental results, thus supporting the appropriateness of the proposed scheme. Simulations of ultra-small MOSFETs demonstrate that the short-range electron – electron and electronion interactions are responsible for the fast thermalization of the carriers at the drain end of the device, which occurs over distances that are on the order of few nanometers. The omission of the short-range portions of these two interaction terms leads to significant overestimation of the distance over which carriers thermalize.